Linear coding of dynamic stimuli by electroreceptor afferents - Gussin, Daniel Jeffrey (University of Ottawa (Canada), 2008)
To determine how sensory receptors respond to signal modulations, we estimated the frequency-intensity (f-I) curves of P-unit electroreceptors using 4 Hz random amplitude modulations (RAMs) and the covariance method (50 Hz RAMs). Both methods showed that P-units are linear encoders of stimulus amplitude with additive noise. The covariance method showed that a linear combination of eigenvectors representing the time-weighted stimulus intensity (E1) and its derivative (E2) could account for 92% of the total response variability. The low gain of the low frequency f-I curve implies that detection of prey would require integration over many receptors and time. Weak signals at the limit of behavioural thresholds could be detected if the animal were able to extract E1 from the population of responding P-units. We propose a tentative mechanism for this operation despite no evidence as to whether it is actually implemented in the nervous system of these fish.
Keywords: Biology, Neuroscience.